1062 GAIT SPEED AND EXECUTIVE PERFORMANCE IN PEOPLE WITH MILD COGNITIVE IMPAIRMENT. (14th June 2022) - Dolphin, H; Fallon, A; McHale, C; Dookhy, J; Kennelly, S P
Abstract: Introduction: The Motoric Cognitive Risk Syndrome has highlighted the link between cognitive and motor performance, and the associated incremental higher risk of developing dementia. There is considerable debate regarding what aspects of cognition (working memory, executive function, attention) are most associated with gait changes. This study investigates the relationship between mobility scores and cognitive profiles in individuals with Mild Cognitive Impairment (MCI) specifically with regard to executive performance and amnestic/non-amnestic profiles. Method: Participants diagnosed with MCI, (Clinical Dementia Rating scale global score of ≤0.5, sum of boxes score ≤ 4.0), attending a regional specialist memory service had a three-meter Timed Up and Go (TUG) gait assessment and multi-domain neuropsychiatric assessment undertaken. Amnestic neuropsychiatric profile was defined as Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) delayed memory subset score < 1SD i.e. ≤16th centile below norm for age/education. Executive function performance was assessed using the Executive Interview (EXIT-25) where higher scores reflect poorer executive performance. Results: Data was reviewed for 161 patients with MCI; 53% (86/161) women. 80% (129/161) had an amnestic neuropsychiatric profile, mean age 73.8 ± 7.2 (51–94). 20% (32/161) had non-amnestic MCI, mean age 74 ± 7.07 (60–87). There was no significant difference in TUG results between amnestic and non-amnestic MCI patients (11.2 ± 3.3 vs 10.7 ± 3.1 p = NS). There was a significant increase in TUG values with worsening executive function performance [EXIT-25 score 0–9 (88/161) mean TUG = 10.5 ± 3.3 seconds vs EXIT-25 score 10–14 (43/161) mean TUG =11.9 ± 2.8 seconds vs EXIT-25 score 15–25 (30/161) mean TUG = 12.1 ± 3.9 seconds; p = 0.021] which persisted after controlling for age, gender and other relevant cofactors. Discussion: Reflective of the importance of frontal lobe integration to the respective tasks, subtle differences in gait performance are associated with executive function performance regardless of predominant amnestic or non-amnestic MCI profile.